European court of justice: practic e and procedure - "Lasok, K. P. E." (London, 1984)
This publication is a complete guide to the practice and procedure of the Court of Justice and the Court of First Instance of the European Communities. It is a detailed explanation of how both Courts work and how cases should be presented, the procedural steps to be followed and the rights of parties in proceedings before both courts. This second edition includes the Practice and Procedure of First Instance and the new verson of the Rules of Procedure of the Court of Justice. Important developments in case law have led to an extensive revision of the text and to the addition of new material, particularly in relation to appeals from the Court of First Instance to the Court of Justice."
Keywords: Court of justice of the European communities